Genome-wide Association Scan Identifies Variants near Matrix Metalloproteinase (MMP) Genes on Chromosome 11q21-22 Strongly Associated with Serum MMP-1 Levels - Cheng, Yu-Ching (2009)
BACKGROUND: Matrix metalloproteinase 1 (MMP-1) may play a role in cardiovascular disease (CVD) susceptibility by influencing plaque rupture via its ability to degrade extracellular collagens. METHODS AND RESULTS: We performed a genome-wide association analysis of circulating MMP-1 levels using 500K SNPs to identify genes influencing variation in serum MMP-1 levels in 778 healthy Amish adults. Serum MMP-1 levels, logarithm-transformed and adjusted for age and sex, were screened for association with SNPs using mixed model variance components to account for familial relatedness. Median MMP-1 level was 3.05 ng/mL (inter-quartile range: 1.82 to 5.04 ng/mL) with an estimated heritability of 81% (P < 0.0001). Serum MMP-1 levels were strongly associated with a cluster of 179 SNPs extending over an 11.5 megabase region on chromosome 11q. The peak association was with rs495366 (P = 5.73 × 10(−34)), located within the region between MMP-1 and MMP-3 and having a minor allele frequency of 0.36. Two other SNPs within the 11q region, rs12289128 and rs11226373, were strongly associated with MMP-1 levels after accounting for rs495366 (P ≤ 10(−7)). These three SNPs explained 31% of the variance in MMP-1 levels after adjusting for age and sex. CONCLUSIONS: The study provides strong evidence that serum MMP-1 level is highly heritable and that SNPs near MMPs on chromosome 11q explain a significant portion of the variation in MMP-1 levels. Identification of the genetic variants that influence MMP-1 levels may provide insights into genetic mechanisms of CVD.